Osteoimmunology of Bone Loss in Inflammatory Rheumatic Diseases - Coury, Fabienne; Peyruchaud, Olivier; Machuca-Gayet, Irma (Frontiers in Immunology, 2019)
Over the past two decades, the field of osteoimmunology has emerged in response to a range of evidence demonstrating the reciprocal relationship between the immune system and bone. In particular, localized bone loss, in the form of joint erosions and periarticular osteopenia, as well as systemic osteoporosis, caused by inflammatory rheumatic diseases including rheumatoid arthritis, the prototype of inflammatory arthritis has highlighted the importance of this interplay. Osteoclast-mediated resorption at the interface between synovium and bone is responsible for the joint erosion seen in patients suffering from inflammatory arthritis. Clinical studies have helped to validate the impact of several pathways on osteoclast formation and activity. Essentially, the expression of pro-inflammatory cytokines as well as Receptor Activator of Nuclear factor κB Ligand (RANKL) is, both directly and indirectly, increased by T cells, stimulating osteoclastogenesis and resorption through a crucial regulator of immunity, the Nuclear factor of activated T-cells, cytoplasmic 1 (NFATc1). Furthermore, in rheumatoid arthritis, autoantibodies, which are accurate predictors both of the disease and associated structural damage, have been shown to stimulate the differentiation of osteoclasts, resulting in localized bone resorption. It is now also evident that osteoblast-mediated bone formation is impaired by inflammation both in joints and the skeleton in rheumatoid arthritis. This review summarizes the substantial progress that has been made in understanding the pathophysiology of bone loss in inflammatory rheumatic disease and highlights therapeutic targets potentially important for the cure or at least an alleviation of this destructive process.